2003
DOI: 10.1053/jhep.2003.50035
|View full text |Cite
|
Sign up to set email alerts
|

Development of antibody to hepatitis B surface antigen after liver transplantation for chronic hepatitis B

Abstract: Patients with chronic hepatitis B virus (HBV) infection have a defective HBV-specific immune response, and the spontaneous development of antibody against hepatitis B surface antigen (anti-HBs) after liver transplantation has not been observed. We report the spontaneous production of anti-HBs in 21 of 50 (42%) patients receiving lamivudine monoprophylaxis after liver transplantation. Seroconversion to anti-HBs status (>10 mIU/mL) was found at a median of 8 days (range, 1 to 43 days) after transplantation. In e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 41 publications
2
64
0
Order By: Relevance
“…Lamivudine therapy was discontinued 1 year after DLT, maintaining HBIG prophylaxis. However, their protocol seems exceptional, and indefinite lamivudine use 3,4,[22][23][24] after DLT is now in trend. In a recent study, 3 47 patients underwent DLT and were administered lamivudine indefinitely.…”
Section: Discussionmentioning
confidence: 99%
“…Lamivudine therapy was discontinued 1 year after DLT, maintaining HBIG prophylaxis. However, their protocol seems exceptional, and indefinite lamivudine use 3,4,[22][23][24] after DLT is now in trend. In a recent study, 3 47 patients underwent DLT and were administered lamivudine indefinitely.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have demonstrated that in chronic HBV-infected patients receiving liver transplantation, the adoptive HBV humoral immunity from donors potentially clears the residual virus and protects the liver graft from HBV reinfection. [6][7][8][9] In lymphoma patients with HBV infection, treatment with rituximab (a chimeric mouse human monoclonal antibody (mAb) against CD20 that induces profound and durable B-cell depletion) significantly increases HBV reactivation. [10][11][12][13] Indeed, antiHBsAg antibodies (HBsAb) can neutralize circulating HBsAg and clear infectious HBV particles in vivo, and the presence of HBsAb in serum is considered an indicator of the resolution of chronic HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, HBsAg seroclearance in Chinese nontransplant patients receiving lamivudine has never been described. HBsAg seroclearance in Chinese patients receiving lamivudine has been reported only for patients with either bone marrow or liver transplantation (5,7,8). In these patients, the HBsAg seroclearance is most likely not related to lamivudine but due to adoptive immunity transfer from the donors (5,7,8).…”
mentioning
confidence: 99%